Teoria jus-humanista multidimensional do trabalho sob a perspectiva do capitalismo humanista - Duarte, Juliana Ferreira Antunes (2014)
This thesis analyzes labor according to a multidimensional view, from an anthropological perspective inserted in humanistic capitalism, in order to position it in Law. It also establishes a rescue of the genesis of the meaning of labor and its legal consecration from the universal acceptance of human rights in all their dimensions, aiming to realize its corresponding goal, the dignity of the human person. This paper argues that it is entitled to Law establish a new vision of human labor, pillar of a humanistic capitalism, which values what men have as innate and external: their workforce, respecting the dignity of the human person by the composition embodied in the dimensions of human rights of freedom, equality and fraternity. The proposal involves the construction of a multidimensional theory of human labor, from the perspective of humanistic capitalism, using the method of normative jus-humanism, which recognizes capitalism as the prevailing and most efficient system known by men, under the aegis and protection of human rights in all their dimensions, interdependent and indissoluble